The Imperative for Strengthening Soil Information Systems in Africa: Reflections and Key Insights from Practice - African Union Development Agency, NEPAD (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This brief highlights the urgent need to enhance soil information systems (SISs) to address Africa’s interconnected challenges of land degradation, climate change, food insecurity, and biodiversity loss. Drawing on insights from Kenya, Malawi, Tanzania, and regional efforts, the brief explores how well-designed SISs can support data-driven decision-making at sub-national, national, and regional levels. It examines the current landscape of soil data systems, showcases practical examples such as the Makueni County Resource Hub and the West Africa Regional Soil Hub, and emphasizes the importance of integrating and aligning soil health indicators in continental policy frameworks including the Nairobi and Kampala Declarations, the Africa Fertilizer and Soil Health (AFSH) Action Plan (2023–2033), and the Ten-Year Comprehensive Africa Agriculture Development Programme (CAADP) Strategy and Action Plan (2026–2035).